Hope, future work self and life satisfaction among vocational high school students in China: The roles of career adaptability and academic self-efficacy. (December 2022) - Zeng, Qing; He, Yingshi; Li, Jia; Liang, Zhengyan; Zhang, Minqiang; Yi, Da; Quan, Jiaxin
Abstract: The current study examined the role of career adaptability and academic self-efficacy as two potential mediators between hope, future work self, and life satisfaction. A total of 636 Chinese vocational high school students completed measures of hope, future work self, career adaptability, academic self-efficacy, and life satisfaction. The results indicated that: (a) hope, future work self, career adaptability, and academic self-efficacy were positively related to life satisfaction; (b) the effects of hope and future work self on life satisfaction were mediated by career adaptability or academic self-efficacy; (c) more hope and clearer future work self were associated with greater career adaptability, which related to higher academic self-efficacy; ultimately, higher academic self-efficacy was related to higher life satisfaction; (d) males tended to report more hope, greater career adaptability, higher academic self-efficacy, and higher life satisfaction than females. These findings contribute to a comprehensive understanding of the factors that intervene in vocational high school students' life satisfaction and enrich theoretical implications about career adaptability.